Cherrapunjee's Forest-fire: Need Immediate Control Measure - Gogoi, B.; Borah, R. K. (Indian Forester, 2010)
Forest Fire, an anti environmental human activity, is becoming a great threat for eco restoration of Cherrapunjee-the site famous as wettest place on earth. Human's carelessness, negligence and ignorance are the main causes of annual ground fire resulting into pronounced and prolonged ill effect on climate, land use, land cover, biodiversity and forest ecosystem. There is an urgent need of fire management practices based on scientific technology, where emphasis should be given on people's participation through Joint Forest Management Programme.